Step-by-step explanation:
Hey, there!!
To solve this type of equation it is very easy from elimination method,
- Firsty, you try to search if there is opposite sign of same variables or not in both equation.
- Then find their LCM to make easy to cancel.
- And thirdly add or subtract the terms to get value of one variable.
- Then substitute the value of one variable to get value of another variable.
Here, the given equation are,
-9x+10y = -18..........(i)
3x-y = 6....................(ii)
Let's take LCM to solve for x.
To solve for "x" we must cancel "y".
LCM= 10 { lcm of 1 and 10 is 1}
So, let's multiply equation (ii) by 10 and add them.
Then,
-9x + 10y = -18
30x - 10y = 60
21x = 42 { as +10y and -10y gets cancelled}
![x = (42)/(21)](https://img.qammunity.org/2021/formulas/mathematics/high-school/x0uuxu2nhowzowc7jvym7u1ggppy9avlbg.png)
Therefore, x= 2.
Substituting the value of x in equation (i)
-9x + 10y = -18
-9 × 2 +10y = -18
-18 + 10y = -18
or, 10y = -18 +18
Therefore, y= 0.
So, the value of x is 2 and y is 0.
Hope it helps...